2015
DOI: 10.1002/anie.201507356
|View full text |Cite
|
Sign up to set email alerts
|

The Trifluoromethyl Anion

Abstract: First evidence for the existence of free trifluoromethyl anion CF3 (-) has been obtained. The 3D-caged potassium cation in [K(crypt-222)](+) is inaccessible to CF3 (-) , thus rendering it uncoordinated ("naked"). Ionic [K(crypt-222)](+) CF3 (-) has been characterized by single-crystal X-ray diffraction, solution NMR spectroscopy, DFT calculations, and reactivity toward electrophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
86
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(101 citation statements)
references
References 28 publications
15
86
0
Order By: Relevance
“…All these warning signs prompted us to have ac loser look at the submitted diffraction data and subsequently to undertake ac omplete re-determination of the structure based on Grushin's data set. À ,asp ublished recently by Grushin et al, [5] (CCDC 1417273).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…All these warning signs prompted us to have ac loser look at the submitted diffraction data and subsequently to undertake ac omplete re-determination of the structure based on Grushin's data set. À ,asp ublished recently by Grushin et al, [5] (CCDC 1417273).…”
Section: Resultsmentioning
confidence: 91%
“…The description of the X-ray structure determination of [K(crypt-222)] + CF 3 À in the paper under discussion already revealed several inconsistencies. [5] It starts with the incorrectly reported crystal system ("hexagonal" for at rigonal space group) and continuest ob eing overly descriptivea nd unnecessarily verbose about how exactly the crystals were harvested from the crystallization vials, while omitting vital information about data reduction such as absorption correction, the scaling procedure, and resolution ranges. The authors mention technical difficulties in mounting as ingle crystal:" multiple crystals rather than as ingle one were mounted on the goniometer head"; [5] however,adescription of how they proceeded with data reduction is not provided.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using DFT to calculate the CF 3 binding affinity of over 40 Lewis acids, the authors of this work were able to narrow in on an ideal regime where the Lewis acid additive provides just enough stabilization to keep CF 3 -from decom posing, yet reactive enough to be used as a reagent. "The best Lewis acid, hexamethylborazine [B 3 N 3 (CH 3 ) 6 ], appears in many chemistry textbooks as an 'inorganic benzene' yet has few applications as a reagent in organic synthesis," said Pro fessor Szymczak, whose lab had previous experience working with borazines for energystorage related projects: "The very challenge we had been facing in our previous investigations with borazines -delivering anionic nucleophiles -suggested they might be perfect candidates for CF 3 -generation/capture/ release experiments because they are very weak Lewis acids," he added. Professor Szymczak and coworkers found that using the borazine Lewis acid facilitated the preparation of highly nucleophilic CF 3 -transfer reagents from HCF 3 in quan titative yield at room temperature.…”
Section: Literature Coverage Synformmentioning
confidence: 99%